Pengetahuan Perawat Terhadap Pencegahan Risiko Jatuh pada Pasien di Ruang Rawat Inap Rumah Sakit Slamet Riyadi Solo - Pratama, Ridho Adhiviko; Artistin, Adisty Rose (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2025)
AbstrakFall risk is an event where a patient is at high risk of experiencing a fall, especially in the elderly with certain health conditions. Falls can cause serious impacts, such as injury or death. Nurses' knowledge plays a crucial role in preventing the risk of falls in patients. The purpose of this study was to determine the relationship between nurses' knowledge and fall risk prevention in patients in the inpatient ward of Slamet Riyadi Hospital, Solo. This type of research is quantitative with a correlational method. The sample used was 73 nurses from the inpatient ward of Slamet Riyadi Hospital, Solo, using the total sampling method. The results of the analysis using the static Pearson test showed a p-value <0001 with an r-value of 0.609, which can be interpreted as a relationship between nurses' knowledge and fall risk prevention in patients in the inpatient ward.